RELATIONSHIP BETWEEN OBESITY AND BREAST CANCER - Bello, Pedro Paulo Dal; Coelho, Carla Cibelle Rosa; Rapatoni, Liane; Peria, Fernanda Maris (Mastology, 2018)
Obesity is a growing clinical condition around the world, considered a risk factor for numerous diseases such as hypertension, myocardial infarction, diabetes, and cancer. Among the neoplasms related to overweight, breast cancer stands out. Therefore, the objective of this review is to elucidate the impact of obesity on the most prevalent cancer among women, either as a direct risk factor for its onset or as a determinant of survival.